Efektivitas Komunikasi Masyarakat dalam Memanfaatkan Pertunjukan Wayang Purwa di Era Globalisasi (Kasus: Desa Bedoyo, Gunung Kidul, Yogyakarta) - A. Saleh; N. Rizkawati (Institut Pertanian Bogor, 2009)
This research aimed to analyze the effectiveness of “Wayang Purwa” to communicate to the society in the era ofglobalization. The analysis designed to reveal the individual characteristics who watch “Wayang Purwa” show, thecharacteristics of “Wayang Purwa” show, the effectiveness using “Wayang Purwa” to communicate with the society,the relationships between individual characters with “Wayang Purwa” performance, and the relationships between“Wayang Purwa” performance with the communication effectiveness to the society especially at Desa Bedoyo,Gunung Kidul, Yogyakarta in environmental cleanness issues. Respondents (79 sample) were selected by simplerandomize sampling, the survey was designed with statistically correlation descriptive model and the statisticanalysis was conducted using descriptive analysis rank Tau Kendall and chi square. This research revealed:Individual characteristics have a significant correlation with the “Wayang Purwa” performance, i.e. (1) ages withmain character, (2) education level with Dalang-Audience interaction, (3) job with main character and main conflict,and also very significant in (a) education level with topics, main character, and main conflict, (b) income with topics,main character, and main conflict, (c) TV watch rate with Dalang-Audience correlation, main character, topics andmain conflict. Respondent individual characters have a significant correlation with them i.e. gender with knowledgeand very significant correlation with the effectiveness of using “Wayang Purwa” to communicate with them i.e. (a)education level with communication effectiveness (b) job with society attitude (c) income with communicationeffectiveness (d) TV watch rate with communication effectiveness. “Wayang Purwa” performance characters have avery significant correlation with the society communication effectiveness.